Dinamika Kepemimpinan Lintas Generasi di Era Hybrid Work: Studi Fenomenologi pada Perusahaan Multigenerasi - Kurniawan, Agung Widhi (PT Maju Malaqbi Makkarana, 2025)
This study explores cross-generational leadership dynamics in hybrid work environments within multigenerational companies in Makassar City. Using a qualitative phenomenological approach, the research examines how leaders adapt to the characteristics of Baby Boomers, Gen X, Millennials, and Gen Z within the local cultural context. Findings reveal that effective leadership in the hybrid era requires an adaptive approach that combines technological flexibility with sensitivity to local cultural values such as siri’ na pacce (honor and solidarity). The study identifies key challenges, including digital divides and intergenerational expectation gaps, while proposing practical solutions such as mentoring rotations and human-centered hybrid work policies. The research implications include recommendations for developing generationally and culturally based leadership training programs, as well as inclusive hybrid work policy models for Eastern Indonesia.